ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEDALAMAN JANGKAUAN (DEPTH OF OUTREACH) LEMBAGA KEUANGAN MIKRO DI KABUPATEN SLEMAN - Purwaningsih Handayani; Lincolin Arsyad (KINERJA, 2013)
The study analyses the factors affecting the depth of outreach of micro nance institutions at Sleman District,Yogyakarta. This study uses quantitative approach with weighted least square- xed effect method of panel dataand primary data obtained from ten BPRs from in the period of 2005-2007. Nine variables used in the processof estimation which are the age of BPR, ROA, number of clients, intermediary variable, number of branch,number of staffs, cost of loans, agriculture sector clients, and trading sector clients. The results of this studyshow that the depth of outreach are statistically signi cant in uenced by ROA, number of branch, cost of loans,agriculture sector clients, and trading sector clients. However, only ROA and trading sector clients that havepositive in uences on the depth of outreach.Keywords : Micro nance, depth of outreach, microentrepreneurs, xed effect method of panel data